SONOGRAPHIC MARKERS IN THE EARLY DETECTION OF RENAL DYSFUNCTION IN DIABETIC ADULTS (Journal of Medical & Health Sciences Review, 2025)
Objective: This study aimed to use the sonographic markers in the early detection of renal dysfunction in diabetic adults.                                                                                                           Study design: The study design was cross sectional in nature.Place and duration of study: The study was conducted at Allied Hospital Faisalabad. Duration of study was 4 months from November 2024 to February 2025.Material and methods: The current study comprised a sample of 250 persons. All diabetic adults (aged18-90) all BMI categories and both genders were consenting before participation, experienced ultrasonography collected their demographic, anthropometric data and blood samples collection. The data was presented as mean and standard deviation (mean ±SD). One-way analysis of variance (ANOVA) was used to calculate the statistical analysis, and the Pearson correlation coefficient was computed for bivariate associations. The statistical significance was established at the 5% (p